Composición de los subproductos de trigo utilizados en la alimentación animal en Costa Rica - Vargas-González, Emilio (Universidad de Costa Rica, 2013)
Composition of wheat by-products used as feed stuffs in Costa Rica. This study was conducted to estimate the nutritional content and their variability of different wheat and bakery by products used as feedstuffs in Costa Rica. Wheat shorts, middlings and brand were studied as well as cookies, crackers and bread. Results clearly indicated that wheat shorts had the highest nutritional value, due to its low fiber and ashes content as well as its high protein, non structural carbohydrates and energy values. Wheat shorts protein levels, NDF, NSC and DE for swine were 79.4;29.7; 45.7% and 3.570 Kcal/kg; for wheat brand values were 18.6; 49.7;24.0% and 2.878 Kcal/kg respectively. Bakery by products (crackers and cookies) showed the highest content of nutrients with high fat levels, NSC and DE for swine (13.1; 77.66% and 4.454 Kcal/kg). The greatest variability in the nutrients content was observed in the ether extracts of the bakery by products. Therefore, it was concluded that all these materials are good nutrient sources for swine, but fiber, fat and energy could vary, indicating that quality control of them should be carefully monitored.